Strain softening of nano-scale fuzzy interfaces causes Mullins effect in thermoplastic polyurethane. - Sui, T; Salvati, E; Ying, S; Sun, G; Dolbnya, IP; Dragnevski, KI; Prisacariu, C; Korsunsky, AM (Nature Publishing Group, 2017)
The strain-induced softening of thermoplastic polyurethane elastomers (TPUs), known as the Mullins effect, arises from their multi-phase structure. We used the combination of small- and wide- angle X-ray scattering (SAXS/WAXS) during in situ repeated tensile loading to elucidate the relationship between molecular architecture, nano-strain, and macro-scale mechanical properties. Insights obtained from our analysis highlight the importance of the 'fuzzy interface' between the hard and soft regions that governs the structure evolution at nanometre length scales and leads to macroscopic stiffness reduction. We propose a hierarchical Eshelby inclusion model of phase interaction mediated by the 'fuzzy interface' that accommodates the nano-strain gradient between hard and soft regions and undergoes tension-induced softening, causing the Mullins effect that becomes apparent in TPUs even at moderate tensile strains.